Peran Bidlabfor Polda Riau Dalam Mengungkap Modus Operandi Pemalsuan Nomor Seri Kendaraan Melalui Pemeriksaan Metalurgi (Studi Kasus Unit II Bidlabfor Polda Riau) - Risxi Rido Pangestu; Riky Novarizal (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
Serial numbers are a series of numbers and letters printed on a metal surface, either on the frame or chassis, or on the engine surface of a motor vehicle. These numbers are created by manufacturers as a means of identification and control, both physically and administratively. In practice, however, vehicle serial numbers are often falsified to deceive law enforcement officers as a modus operandi in vehicle theft. This issue becomes the main focus of this research. Using a qualitative method with in-depth interviews involving selected informants, this study reveals that perpetrators of serial number forgery commit crimes based on rational considerations, namely profit and loss calculations aimed at maximizing personal financial gain. Offenders replace the serial numbers of stolen vehicles to prevent detection, believing that the economic benefits outweigh the risk of arrest and punishment. Meanwhile, metallurgical examination by Bidlabfor Polda Riau proves highly effective in detecting metal-related criminal indications in serial number forgery. Forensic metallurgy serves as a scientific approach to examine and collect physical evidence found at the crime scene, ensuring its admissibility as valid scientific proof in court proceedings, thereby strengthening the role of forensic science in modern criminal investigation.